Increasing Engineers’ Role in Construction Safety: Opportunities and Barriers (Salam International Academic Journal, 2022)
A number of factors suggest engineering and Construction professionals should discuss increasing designer’s role in construction safety. Design civil engineer could contribute to construction worker safety by performing five tasks differently than current custom and practice: reviewing their designs, creating design documents, assisting the owner in procuring construction, reviewing submittals, and inspecting work in progress. However, four sets of major barriers would prevent designers from increasing worker safety through these tasks: lack of safety expertise, lack of understanding of construction processes, typical contract terms, and professional fees. Potential ways for reducing these barriers are suggested. Some regulation like The United Kingdom regulations requiring engineers to design for safety are summarized, but it is concluded that similar legislation in the United States would not be appropriate.
Keywords: Construction industry; Design Criteria; Safety; Regulation